Nghiên cứu quy trình phân hủy nhiệt tinh quặng đất hiếm basnezit Đông Pao với axit sunfuric - Nhuận, Hoàng; Đĩnh, Lưu Xuân; Tùng, Nguyễn Văn; Thuận, Lê Bá; Sơn, Lê Hải (Vietnam Journal of Chemistry, 2015)
Bastnasite ore is one of most important rare earth ore, with main component is light rare earth from La to Nd. In Viet Nam bastnasite Dong Pao, Lai Chau province has been estimated with over million metric tons. Nowadays, a technical sulfating rare earth ore has developed to get total rare earth oxide. For this process gotten rare earth oxide will be higher purification and recovery than other processes, oxidation roasting, leaching ore etc. In this study, bastnasite ore mixed with sulfuric acid and then curing at room temperature after that the mix was put in electric furnace and heat to 450÷550 oC to estimate the recovery of rare earth. The roasting time was investigated range 2 to 3.5 hours. The result showed that the best condition for sulfating rare earth ore process is roasting time 2h at 550 oC, at this condition the recovery of rare earth is highest. The mineral and chemical component of ore and product, respectively have been determined by X-ray Diffraction (XRD) and ICP-OES.